Discrete‐time modelling and stability analysis of wireless power transfer system. Issue 13 (23rd July 2021) - Hu, Xiufang; Wang, Yue; Ma, Tianlu; Lyu, Shuangqing; Gao, Guoqing; Lei, Wanjun
Abstract: Wireless power transfer (WPT) has been widely used in recent years due to its convenient access to power and security in some specific cases. However, the inherent non‐linearity of the WPT system can result in unexpected stability problems. In this paper, the stability issue of voltage‐mode controlled inductor‐capacitor‐capacitor and series (LCC/S) compensated WPT system is studied for the first time. The discrete‐time model is first introduced to establish the voltage‐mode proportional (P) controlled and proportional integral (PI) controlled LCC/S compensated WPT system. Meanwhile, a modelling method of PI controller without introducing new state variables is proposed in this paper. Then, with the bifurcation diagram and eigenvalues of the Jacobian matrix, the stability of the LCC/S compensated WPT system is analysed with respect to the proportional coefficient and integral coefficient of the controller. Furthermore, by studying the eigenvalues of the Jacobian matrix, the stability boundary can be obtained. In addition, how the load and mutual inductance affect the stability boundary is investigated compressively, the law of influence provided by the operating condition upon the stability can be concluded. Finally, simulation and experimental measurements are provided to verify the accuracy of the discrete‐time model and the effectiveness of the theoretical stability analysis.